(untitled) - Quinlan, Marsha B.; Marsha B. Quinlan (Belmont, CA, 2004)
Importance of home remedies -- Dominica and Dominicans -- Bwa Mawego -- Methods -- Disease and illness in Bwa Mawego -- Bwa Mawego's sectors of health care -- Body image in Bwa Mawego -- Bush medicine in Bwa Mawego: illnesses and their treatments -- Applications and conclusions -- Glossary
Keywords: Botany; Medical; Traditional medicine